Exercise-induced cardiac troponin T release: A meta-analysis. - Shave, R.; George, K. P.; Atkinson, G.; Hart, E.; Middleton, N.; Whyte, G.; Gaze, D.; Collinson, P. O. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Cardiac troponin T (cTnT) is a highly specific marker of myocardial damage and used clinically in the diagnosis of acute myocardial infarction (AMI). Release of cTnT has been demonstrated in several small studies after endurance exercise. The purpose of this study was to explore, using a meta-analytic approach, the incidence of postexercise cTnT release after endurance exercise.